U.S. Forest Service citizen science: improving monitoring capacity, ecological literacy and outreach - Pitt, Aleksandra N., author; Schultz, Courtney, advisor; Vaske, Jerry, committee member; Fernandez-Gimenez, Maria, committee member (Colorado State University. Libraries, 2016)
The Forest Service is integrating citizen science projects and data into the management of national forests around the country. I selected three citizen science projects that involve the Forest Service collaborating with secondary school students in direct field collection of monitoring data to: understand the objectives and design of the programs, determine the impacts on participants; and identify the benefits, if any, for the agency. I conducted eight interviews with the project leads and teachers to understand their goals, design, and objectives for the program. To determine the impacts to the participants I interviewed and surveyed 25 current students before and after their participation in the project. I also interviewed five students who participated in the projects in previous years. My findings show that both students and the agency achieved their desired outcomes for beginning the citizen science projects. I found that the objectives and design of these programs have a significant influence on student outcomes and should be designed with objectives in mind. My findings suggest enhanced ecological literacy is a potential outcome of these youth based, citizen science monitoring programs. I found evidence of increased environmental stewardship, although I was unable to determine whether this persists. The projects experienced some minor challenges with the students' data reliability; however, project leads and students alike concluded that these projects, although they did produce valuable data, had greater value for the relationships built between students and the agency, their teachers, and the natural world.